MYSTERY BOX AND ITS IMPACT ON SOCIETY (ISLAMIC LAW REVIEW) - Nurfyana Narmia Sari; Muslimin Kara; Rahmawati Muin (Pascasarjana UIN Alauddin Makassar, 2021)
The main problem of the research is How is the Impact of Buying and Selling Mystery Boxes and the Impact on Shopee E-Commerce Consumers in Makassar City (Review of Islamic Law? The subject matter is further elaborated into sub-problems, namely: 1) what is the nature of buying and selling Mystery Box? 2) What is the Impact of Buying and Selling Mystery Box e-commerce to consumers in Makassar City? 3) What is the Law of Buying and Selling Mystery Box in E-commerce based on Islamic Law?. The type of research used is qualitative by using a research approach, namely: Juridical Phenomenology Approach, and Shari'a Normative Approach. Then the source of this research data is taken from primary data in the form of interviews with customers of Mystery Box Angela Beauty Makassar, and secondary data in the form of data taken from costumers Angela Beauty and literature studies related to the problems studied. Furthermore, the data collection methods used were observation, interviews, and documentation as well as other reference searches. The data processing and data analysis techniques were carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study indicate that the impact of buying and selling Mystery Boxes in Makassar City has a major impact on customers who have already purchased mystery boxes. Some of the customers who have bought the mystery box but did not get the product according to the selling price, but instead got the product that was not worth the purchase price. The seller is not responsible for the customer's loss because the seller has provided a product description if buying a mystery box, the prospective customer has agreed to the type, color and shape of the goods received, this is contrary to Islamic law because legal buying and selling must not have an element of uncertainty (gharar) and chancy (Maysiir). In addition, protection against consumers regarding consumer rights does not apply when buying a mystery box because the seller does not accept the return of the goods.